(untitled) (DAPesquisa, 2021)
This article aims to understand how African fabrics can be instruments of anti-racist struggles in Brazilian society. Specifically, the reflections conducted throughout this article were based on Ofi/Pano da costa, Adinkra and Wax, three fabrics that refer to Africa and that have significant importance in Brazil as a symbolic and identity repertoire of black people. As a methodological subterfuge, the research has a qualitative approach, in which three in-depth interviews were conducted with African people, currently resident in Brazil, who know the fabrics and are actively involved in the diffusion of these items in Brazil. In general, the results of the article point to the rich symbolic, identity and cultural repertoire that surround African fabrics, in a dynamic in which the uses of these fabrics (re)connect the black subjects of the diaspora to the ancestral philosophies and cultural traditions of the African people. Therefore, the meanings and uses of fabrics represent important tools for decolonial and anti-racist practices, (re)valuing the multiple legacies of African peoples.